RAG1 oligomerization states and secondary structural properties: an initial characterization of V(D)J recombinase complex formation. Issue 2 (2004) - Godderz Godderz, LeAnn J. LeAnn J.; Rodgers Rodgers, Karla K. Karla K.
Abstract : The recombination activating gene products (RAG1 and 2) catalyze the initial DNA cleavage steps during V(D)J recombination for the diversification of the immune repertoire. As the fundamental properties of the RAG proteins remain largely unknown, our objective is to investigate the self–association and conformational properties of RAG1. To analyze RAG1 association and dissociation, a time course of multi–angle laser light scattering measurements (MALL SEC) was performed on samples at different oligomerization states over a wide range of ionic strengths. The molecular masses of the predominant RAG1 species corresponded to dimer, tetramer, and a previously uncharacterized octamer state. Furthermore, the fraction of RAG1 in the tetrameric and octameric states increased significantly over time at lower ionic strengths, indicating that these oligomeric forms may factor into the physiological function of RAG1. Circular dichroism (CD) analysis of RAG1 showed a significant dependence in secondary structure on ionic strength with changes in α-helical content over time that may correspond to the changes in oligomerization states shown by MALLS SEC. Together, the MALLS SEC and CD analyses of RAG1 self-association properties and secondary structure give further insight into formation of the protein complex responsible for catalyzing V(D)J recombination.